A method for preparing multi-element carbide ceramic nanowires by a molten salt method
Patent Information
- Application Number
- CN202411610536.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-11-12
AI Technical Summary
[0003]然而,多元超高温陶瓷由于晶体结构、原子尺寸和电荷平衡等因素在低温下难以固溶,而高温下制备纳米线又容易受到纳米尺寸效应的影响
[0035]1.本发明的制备方法通过利用金属粉在熔盐中的溶解性,实现了金属粉在熔盐中的均匀分布,并与碳纳米材料发生原位反应,从而制备出多元碳化物陶瓷纳米线。与气相沉积法原位催化生长相比,熔盐原位反应法具有实验步骤简单、粉末成本低、制备周期短等优点。此外,采用本发明方法合成的多元碳化物陶瓷纳米线为单一固溶相,具有物相纯度高、纳米线分布均匀的特点。
Smart Images

Figure CN119263839B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of preparation technology of multi-component carbide ceramic nanowires, specifically a method for preparing multi-component carbide ceramic nanowires by molten salt method. Background Technology
[0002] Compared to bulk ceramics, one-dimensional (1D) nanoceramics have become highly attractive nanomaterials due to their unique 1D characterization and excellent properties, including high aspect ratio, large specific surface area, extremely low dislocation density, superior mechanical properties, and chemical stability. Ultra-high temperature ceramic nanowires have been used to improve interfacial bonding, toughen coatings, and reinforce structural composite materials. Similarly, 1D high-entropy ceramics, due to their small size and unique microstructure, possess excellent physical, chemical, and mechanical properties, demonstrating their potential as toughening materials under high-temperature conditions.
[0003] However, multi-component ultra-high temperature ceramics are difficult to solidify at low temperatures due to factors such as crystal structure, atomic size, and charge balance, while the fabrication of nanowires at high temperatures is easily affected by nanosize effects. This limits the application of 1D HECs as composite materials or ceramic reinforcement materials.
[0004] To address this issue, this invention leverages the advantages of molten salt, which provides a liquid phase environment and ionic melt at lower temperatures. Metal components are dissolved into the molten salt at low temperatures, and an in-situ reaction occurs using carbon nanotubes as templates. This allows for the low-cost synthesis of single-phase, high-purity, multi-component carbide ceramic nanowires at low temperatures. Summary of the Invention
[0005] This invention overcomes the above-mentioned technical problems and provides a method for preparing multi-component carbide ceramic nanowires by molten salt method. The preparation method of this invention is simple, feasible, and can be industrialized. In addition, the multi-component carbide ceramic nanowires prepared by this invention have high phase purity and uniform distribution.
[0006] The present invention solves the above-mentioned technical problems through the following technical solutions.
[0007] This invention discloses a method for preparing multi-component carbide ceramic nanowires by molten salt method, wherein the multi-component carbide ceramic nanowires include the following raw materials: carbon nanotubes, potassium halides and group IVB metal powders;
[0008] The method for preparing multi-component carbide ceramic nanowires by the molten salt method includes the following steps:
[0009] The raw materials are mixed and then sintered.
[0010] In this invention, the mass ratio of group IVB metal powder: carbon nanotubes: potassium halide is 4-9:0.5-1:8-10.5; preferably, the mass ratio of group IVB metal powder: carbon nanotubes: potassium halide is 4.5-8:0.5-1:8.5-10.
[0011] In this invention, the carbon nanotubes (CNTs) have a carbon-based content of ≥95%.
[0012] In this invention, the outer diameter of the carbon nanotube is 10–40 nm.
[0013] In this invention, the length of the carbon nanotube is 0.5 to 1.5 mm.
[0014] In this invention, the potassium halide is KCl and KF.
[0015] In this invention, the mass ratio of KCl to KF in the potassium halide is 8-9:0.5-1.
[0016] In this invention, the IVB metal powder is Zr powder, Hf powder, and Ti powder.
[0017] In this invention, the mass ratio of Zr:Hf:Ti in the group IVB metal powder is 1-2:3-5:0.5-1.
[0018] In this invention, the mass ratio of each component in the carbon nanotubes, potassium halide, and group IVB metal powder is Zr:Hf:Ti:CNT:KCl:KF = 1~2:3~5:0.5~1:0.5~1:8~9:0.5~1; for example, Zr:Hf:Ti:CNT:KCl:KF = 2:3:1:0.5:9:1.
[0019] In this invention, the mixing process also includes a drying operation.
[0020] In this invention, after sintering, the material needs to be cooled to room temperature (20°C) and filtered with water and alcohol respectively to wash away excess molten salt.
[0021] Furthermore, the drying temperature is 100–150°C, for example, 130°C.
[0022] Furthermore, the drying time is 8 to 16 hours, preferably 10 to 12 hours, for example 12 hours.
[0023] Furthermore, the vacuum degree of the drying process is 10 to 90 Pa, for example, 10 Pa.
[0024] In this invention, the heating rate before sintering is 5-15°C / min, preferably 8-12°C / min, for example 10°C / min.
[0025] In this invention, the sintering temperature is 800-950℃, preferably 900-950℃, for example 900℃ or 950℃.
[0026] In this invention, the sintering time is 1 to 5 hours, preferably 1 to 3 hours, for example 1 hour;
[0027] In this invention, the vacuum degree of the sintering is 10-90 Pa, preferably 10-50 Pa, for example 10 Pa.
[0028] In this invention, the room temperature is 20-25°C, for example, 20°C.
[0029] In this invention, after cooling to room temperature, the mixture needs to be filtered three or more times with water and alcohol respectively to wash away excess molten salt.
[0030] In this invention, the multi-component carbide ceramic nanowires comprise a single-phase solid solution.
[0031] In this invention, the composition of the multi-component carbide ceramic nanowires includes (Zr) a Hf b Ti c C d Wherein, a = 2–9 at% , b = 2–7 at% , c = 2.5–15 at% , and d = 45–75 at% ; preferably, a = 2.5–6.8 at% , b = 2.5–6.5 at% , c = 2.5–13.5 at% , and d = 48–73 at%.
[0032] The aforementioned molten salt method for preparing multi-component carbide ceramic nanowires has applications in the fields of toughening materials, thermal insulation materials, or protective materials.
[0033] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.
[0034] Compared with the prior art, the beneficial effects of the present invention are:
[0035] 1. The preparation method of this invention utilizes the solubility of metal powder in molten salt to achieve uniform distribution of the metal powder in the molten salt, and then allows it to react in situ with carbon nanomaterials, thereby preparing multi-component carbide ceramic nanowires. Compared with in-situ catalytic growth via vapor deposition, the molten salt in-situ reaction method has advantages such as simple experimental steps, low powder cost, and short preparation cycle. Furthermore, the multi-component carbide ceramic nanowires synthesized using this method are a single solid solution phase, exhibiting high phase purity and uniform nanowire distribution.
[0036] 2. The multi-component carbide ceramic nanowires prepared by the method of this invention not only exhibit uniform physical distribution but also high phase purity and uniform elemental distribution. Since no substrate or catalyst is required during the preparation process, the resulting nanowires possess very high purity. Multi-component carbides can be directly applied to C / C composite materials, graphite matrices, and other substrates, and can also be used for toughening multi-component ultra-high temperature ceramic bulk materials.
[0037] 3. The preparation method of the present invention is simple, feasible, low-cost, and suitable for industrial production. Attached Figure Description
[0038] Figure 1 This is a scanning electron microscope image of the multi-component carbide ceramic nanowires prepared in Example 1;
[0039] Figure 2 The image shows the BES pattern of the multi-component carbide ceramic nanowires prepared in Example 1.
[0040] Figure 3 This is a scanning electron microscope image of the multi-component carbide ceramic nanowires prepared in Example 2;
[0041] Figure 4 The image shows the BES pattern of the multi-component carbide ceramic nanowires prepared in Example 2.
[0042] Figure 5 The image shows a scanning electron microscope (SEM) image of the multi-component carbide ceramic nanowires prepared in Comparative Example 1.
[0043] Figure 6 BES image of the multi-component carbide ceramic nanowires prepared in Comparative Example 1.
[0044] Figure 7 This is a scanning electron microscope image of the multi-component carbide ceramic nanowires prepared in Comparative Example 2.
[0045] Figure 8 The image shows the BES pattern of the multi-component carbide ceramic nanowires prepared in Comparative Example 2.
[0046] Figure 9 The image shows the XRD pattern of the multi-component carbide ceramic nanowires prepared in Example 1. Detailed Implementation
[0047] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0048] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0049] The "range" disclosed in this invention is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be combined arbitrarily; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for specific parameters, it is understood that ranges of 60-110 and 80-120 are also expected. Furthermore, if minimum range values 1 and 2 are listed, and if maximum range values 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this invention, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed herein; "0-5" is merely a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer greater than or equal to 2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0050] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0051] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0052] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0053] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0054] Unless otherwise specified, the term "or" is inclusive in this invention. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0055] In the following examples and comparative examples, the carbon nanotubes were purchased from Aladdin (the carbon content of the carbon nanotubes (CNTs) was ≥95%; the outer diameter of the carbon nanotubes was 10–40 nm; and the length of the carbon nanotubes was 0.5–1.5 mm).
[0056] Example 1
[0057] 1. Raw materials for preparing the multi-component carbide ceramic nanowires in this embodiment:
[0058] The mass ratio of Zr:Hf:Ti:CNT:KCl:KF is 2:3:1:0.5:9:1.
[0059] 2. Preparation method of multi-component carbide ceramic nanowires in this embodiment:
[0060] S1. Mix and grind carbon nanotubes, potassium halide and group IVB metal powders according to the required ratio to obtain a mixture;
[0061] S2. Dry the mixture at 130℃ for 12 hours to obtain a dried material;
[0062] S3. The dried material is heated to 900℃ at a heating rate of 10℃ / min and sintered at this temperature for 1 hour. After sintering, it is naturally cooled to room temperature. Finally, it is filtered three times with water and alcohol respectively to wash away excess molten salt, and multi-component carbide ceramic nanowires are obtained.
[0063] The scanning electron microscope image of the multi-component carbide ceramic nanowires prepared in this embodiment is shown below. Figure 1 (The "+" in the image indicates the scanned area), see BES diagram. Figure 2 . Figure 1 Uniformly distributed nanowires can be observed. Figure 2 No obvious elemental segregation was observed. EDS results showed that the nanowires contained Zr, Hf, and Ti elements (EDS results showed that this location contained: 72.73 at% C, 19.06 at% O, 2.67 at% Zr, 2.81 at% Ti, and 2.73 at% Hf). Figure 9 The image shows the XRD pattern of the multi-component carbide ceramic nanowires prepared in this embodiment. The XRD pattern shows a set of diffraction peaks indicating that it is a single-phase solid solution.
[0064] Example 2
[0065] The difference between this embodiment and Embodiment 1 is as follows:
[0066] In this embodiment S3, the sintering temperature is 950℃.
[0067] The scanning electron microscope image of the multi-component carbide ceramic nanowires prepared in this embodiment is shown below. Figure 3 See BES diagram. Figure 4 . Figure 3 Uniformly distributed nanowires can be observed. Figure 4 No obvious elemental segregation was observed. EDS results showed that the nanowires contained Zr, Hf, and Ti elements (EDS results showed that the multi-element carbide ceramic nanowires contained: 48.91 at% C, 25.37 at% O, 6.72 at% Zr, 13.04 at% Ti, and 5.97 at% Hf. Due to the rounding error during equipment measurement, the content may be close to but not equal to 100%) and formed a solid solution phase.
[0068] Comparative Example 1
[0069] The difference between this comparative example and Example 1 is as follows:
[0070] In this comparative example S3, the sintering temperature was 1000℃.
[0071] The scanning electron microscope image of the multi-component carbide ceramic nanowires prepared in this comparative example is shown below. Figure 5 (The "+" in the image indicates the selected area), see BES diagram. Figure 6 Combining Figure 5 It is known that the rapid dissipation of molten salt can cause nanowires to clump together; Figure 6 The results showed that the multi-component carbide ceramic nanowires contained 48.46 at% C, 23.99 at% O, 6.80 at% Zr, 14.27 at% Ti, and 6.48 at% Hf, and the three elements Zr, Hf, and Ti were all distributed in the solid, indicating that the coils were still a solid solution.
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is as follows:
[0074] In this comparative example S3, the sintering temperature was 1100℃.
[0075] The scanning electron microscope image of the multi-component carbide ceramic nanowires prepared in this comparative example is shown below. Figure 7 See BES diagram. Figure 8 Combining Figure 7 It is known that the rapid dissipation of molten salt can cause nanowires to clump together; Figure 8The results showed that the multi-component carbide ceramic nanowires contained 54.82 at% C, 19.14 at% O, 8.51 at% Zr, 10.88 at% Ti, and 6.64 at% Hf. Note that due to rounding errors during measurement, the content may appear close to but not equal to 100%. Zr, Hf, and Ti were all distributed in the solid, indicating that the clumps remained a solid solution. Furthermore, the clumping effect intensified with increasing temperature, clearly indicating that temperature primarily affected the morphology and distribution of the nanowires.
[0076] Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in this invention can be purchased commercially or prepared using existing methods. The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of this invention. It should be understood that the above descriptions are merely specific embodiments of this invention and are not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A method for preparing multi-component carbide ceramic nanowires using a molten salt method, characterized in that, The multi-component carbide ceramic nanowires include the following raw materials: carbon nanotubes, potassium halides, and group IVB metal powders. The potassium halides are KCl and KF; The group IVB metal powders are Zr powder, Hf powder, and Ti powder; The method for preparing multi-component carbide ceramic nanowires by the molten salt method includes the following steps: S1. Mix and grind carbon nanotubes, potassium halide and group IVB metal powder to obtain a mixture; S2. Dry the mixture to obtain a dried material; S3. Sinter the dried material at a temperature of 800-950℃. After sintering, cool to room temperature and filter with water and alcohol respectively to wash away excess molten salt, thus obtaining multi-component carbide ceramic nanowires. The multi-component carbide ceramic nanowires comprise a single-phase solid solution.
2. The method for preparing multi-component carbide ceramic nanowires by molten salt method as described in claim 1, characterized in that, The mass ratio of the group IVB metal powder, carbon nanotubes, and potassium halide is 4–9:0.5–1:8–10.
5.
3. The method for preparing multi-component carbide ceramic nanowires by molten salt method as described in claim 1, characterized in that, The mass ratio of KCl to KF in the potassium halide is 8-9:0.5-1; And / or, the mass ratio of Zr:Hf:Ti in the group IVB metal powder is 1-2:3-5:0.5-1.
4. The method for preparing multi-component carbide ceramic nanowires by molten salt method as described in claim 3, characterized in that, The mass ratio of each component in the prepared raw material is Zr:Hf:Ti:CNT:KCl:KF = 1~2:3~5:0.5~1:0.5~1:8~9:0.5~1.
5. The method for preparing multi-component carbide ceramic nanowires by molten salt method as described in claim 1, characterized in that, At least one of the following conditions ① to ③ must be met: ① The drying temperature is 100-150℃; ②The drying time is 8–16 hours; ③ The vacuum degree of the drying process is 10-90 Pa.
6. The method for preparing multi-component carbide ceramic nanowires by molten salt method as described in claim 1, characterized in that, At least one of the following conditions ① to ③ must be met: ①The heating rate before sintering is 5-15℃ / min; ②The sintering time is 1~5h; ③ The vacuum degree of the sintering is 10~90 Pa.
7. The method for preparing multi-component carbide ceramic nanowires by molten salt method as described in claim 6, characterized in that, At least one of the following conditions ① to ④ must be met: ①The heating rate before sintering is 8-12℃ / min; ② The sintering temperature is 900–950℃; ③ The sintering time is 1~3 hours; ④ The vacuum degree of the sintering is 10~50 Pa.
Citation Information
Patent Citations
Method for preparing Ta1 / 3Nb1 / 3Ti1 / 3C ceramic nano-powder by using molten salt method
CN116477951A